Platelet Parameters and Their Relationships With the Thickness of the Retinal Nerve Fiber Layer and Ganglion Cell Complex in Primary Open-Angle Glaucoma - Ma, Yi; Li, Shengjie; Shao, Mingxi; Cao, Wenjun; Sun, Xinghuai (Frontiers in Neurology, 2022)
Objective Glaucoma is a neurodegenerative disease of the visual system. Platelet parameters are correlated with visual field mean deviation (MD) in glaucoma, but there is a lack of relative data on their relationship with structural changes in the retina. This study aimed to explore the relationship between platelet parameters and retinal nerve fiber layer (RNEL), ganglion cell complex (GCC) thickness, and cup/disk area ratio, evaluated by optical coherence tomography (OCT) in primary open-angle glaucoma (POAG). Methods A total of 118 consecutive patients with POAG and 120 age- and sex-matched control subjects were included in this retrospective study. Demographic data, platelet parameters in blood tests, visual field, and OCT results were evaluated. The RNFL was divided into the temporal, superior, nasal, and inferior quadrants. Based on the visual field MD, the patients were stratified into mild (MD ≤ 6.0 dB), moderate (6 dB < MD ≤ 12 dB), and severe (MD > 12.0 dB) subgroups. Results Patients with POAG had significantly lower platelet (PLT) levels and significantly higher platelet distribution width (PDW) and mean platelet volume (MPV) levels than controls. As the visual field MD increased, structural evaluation by OCT identified loss of disk rim area, average GCC thickness, and average RNFL thickness (all P < 0.001), as well as increased PDW (P < 0.001) and MPV (P = 0.004) levels in patients with POAG. The Spearman's rank correlation analysis showed that PDW levels were significantly correlated with OCT parameters such as RNFL thickness (r = −0.370, P < 0.001), GCC thickness (r = −0.294, P = 0.001), and cup/disk area ratio (r = 0.322, P < 0.001), as well as visual field MD (r = 0.607, P < 0.001) and mean sensitivity (MS) (r = −0.570, P < 0.001). Significantly correlations were also found between MPV and RNFL thickness (r = −0.321, P < 0.001), GCC thickness (r = −0.194, P = 0.041), and cup/disk area ratio (r = 0.237, P = 0.010). All the quadrants showed similar negative correlations between PDW, MPV, and RNFL thickness. The multiple linear regression analyses showed significant association between PDW and RNFL thickness (β = −0.331, P < 0.001), PDW and GCC thickness (β = −0.288, P = 0.002), MPV and RNFL thickness (β = −0.313, P = 0.001), and MPV and GCC thickness (β = −0.188, P = 0.048). Conclusion This study found significantly negative association between PDW, MPV levels and RNFL, GCC thickness, as well as positive association between PDW, MPV levels, and cup/disk area ratio in patients with POAG, suggesting that platelet activation may contribute to glaucomatous optic neuropathy.